Abnormally Prolonged Bleeding After an Arthroscopic Knee Reconstruction Because of an Inherited Factor XIII Deficiency: A Case Report. Issue 4 (1st October 2021) - Wattakavanich, Narusorn; Boonrod, Artit; Wanitpongpun, Chinadol; Tharakulphan, Suthee
Abstract : Case: An 18-year-old man developed ecchymosis after arthroscopic anterior cruciate ligament reconstruction with semitendinosus graft and meniscal repair. The results of routine coagulation studies were normal, but factor assays showed a reduction in factor XIII levels. The bleeding symptoms were dramatically improved after administration of cryoprecipitate. Conclusion: Factor XIII deficiency is one of the rare clotting factor deficiencies that can be present at birth or be manifested later in life. Clinical awareness of factor XIII deficiency is essential so that appropriate testing and treatment can be achieved.